Business cycles in emerging markets: The role of liability dollarization and valuation effects - Stefan Notz; Peter Rosenkranz (University of Zurich, Department of Economics, 2014)
Understanding differences in business cycle phenomena between Emerging Market Economies (EMEs) and industrialized countries has been at the center of recent research on macroeconomic fluctuations. The purpose of this paper is to investigate the importance of certain credit market imperfections in different EMEs. To this end, we develop a small open economy Dynamic Stochastic General Equilibrium (DSGE) framework featuring both permanent and transitory productivity shocks, differentiated home and foreign goods, and endogenous exchange rate movements. Furthermore, our model incorporates liability dollarization as a particular form of financial frictions in EMEs. In this vein, weaccount for the fact that emerging markets traditionally have had difficulties in borrowing in domestic currency on international capital markets and thus allow for valuation effects in our analysis. We estimate our model using Bayesian techniques for a number of EMEs and thereby control for potential heterogeneity across countries. Contrary to previous studies in this strand of the literature, we include a (vector-)autoregressive measurement error component to capture off-model dynamics. Regarding business cycles in emerging markets, our main findings are that (i) even though we incorporate financial frictions in the framework, trend shocks are the main determinant of macroeconomic fluctuations, (ii) accounting for liability dollarization ameliorates the model fit, and (iii) valuation effects on average stabilize changes in the net foreign asset position.
Keywords: E13; E44; F32; F34; F41; F44; F47; O11; 330; Emerging Markets; Liability Dollarization; Valuation Effects; Financial Frictions; Real Business Cycles; DSGE Model; Bayesian Estimation